Insights into the rheological modeling of semi-solid metals: Theoretical and simulation study. (20th February 2022) - Ma, Zhen; Zhang, Huarui; Fu, Hanwei; Yang, Yanzhao; Wang, Jianji; Du, Ming; Zhang, Hu
Highlights: The power law model for semi-solid metals suffers major drawbacks. The flow exponents of power law model in (–1/3, 0] are physically nonsensical. The irrational flow exponents stem from neglecting yield stress. The drawbacks cause over-optimistic predictions on blistering and misrun. HB model taking yield stress into consideration is more accurate. Abstract: The power law model is the most widely used model for the rheological behavior of semi-solid metals (SSMs) in the numerical simulation of semi-solid processing. However, it is still not known why the anomalous negative flow exponent exists in the power law model for SSMs and its influence on the simulation. In this research, the rheological behavior of semi-solid Al-7Si-0.3Mg aluminum alloy is experimentally studied followed by modeling. The power law model fitting results show flow curves deviate from the experimental data and negative flow exponents, which are physically nonsensical and inapplicable to the simulation of SSMs flow proved by hydrodynamic analysis. This drawback of the power law model stems from neglecting the yield stress of SSMs. By contrast, the model referring Herschel-Bulkley (HB) theory which takes yield stress into consideration has reasonable flow exponent and yields good agreement between the fitting and experimental results. Furthermore, the simulation of die filling process is conducted, suggesting that the power law model over-optimistically predicts the tendency of blistering and misrun defects at low temperature and high filling velocity during semi-solid processing. Graphical abstract: Image, graphical abstract